2018
DOI: 10.1016/j.jacr.2018.03.020
|View full text |Cite
|
Sign up to set email alerts
|

ACR Appropriateness Criteria ® Pretreatment Staging of Muscle-Invasive Bladder Cancer

Abstract: Muscle-invasive bladder cancer (MIBC) has a tendency toward urothelial multifocality and is at risk for local and distant spread, most commonly to the lymph nodes, bone, lung, liver, and peritoneum. Pretreatment staging of MIBC should include imaging of the urothelial upper tract for synchronous lesions; imaging of the chest, abdomen, and pelvis for metastases; and MRI pelvis for local staging. CT abdomen and pelvis without and with contrast (CT urogram) is recommended to assess the urothelium and abdominopelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…Most often, this is applied to the setting of MIBC where the risk of pelvic lymph node metastases is far greater than that for NMIBC and useful for preoperative risk stratification (Figure 3). The current ACR Appropriateness Criteria for the pretreatment staging of MIBC rate FDG-PET/CT as "may be appropriate" [49]. Traditionally, FDG-PET/CT for bladder cancer has been limited by a number of factors, including false-positive findings due to inflammation and obscuration of the urinary bladder by radiotracer activity in excreted urine.…”
Section: Fdg-pet/ct For Bladder Cancer Stagingmentioning
confidence: 99%
“…Most often, this is applied to the setting of MIBC where the risk of pelvic lymph node metastases is far greater than that for NMIBC and useful for preoperative risk stratification (Figure 3). The current ACR Appropriateness Criteria for the pretreatment staging of MIBC rate FDG-PET/CT as "may be appropriate" [49]. Traditionally, FDG-PET/CT for bladder cancer has been limited by a number of factors, including false-positive findings due to inflammation and obscuration of the urinary bladder by radiotracer activity in excreted urine.…”
Section: Fdg-pet/ct For Bladder Cancer Stagingmentioning
confidence: 99%
“…Utilizing these techniques, authors report sensitivities between 50 and 96% (9)(10)(11)(12)(13)(14)(15)(16)(17). However, to date, 18F-FDG PET/CT has not be shown to improve primary tumor detection and staging, when compared to cystoscopy and morphological imaging alone performed with CT and especially MRI (18).…”
Section: Risk Stratification At Diagnosismentioning
confidence: 99%
“…In conclusion, the current literature suggests that 18F-FDG PET/CT provides an incremental value for nodal and distant staging in MIBC at initial diagnosis. However, due to its significant cost for healthcare systems (34), prospective studies with high evidence level are still needed before its use can be formally adopted into consensus guidelines and recommendations (3,18,35,36). In support of its role in distant staging, a recent consensus statement revealed that 18F-FDG PET/CT is the imaging modality of choice to avoid overtreatment in oligometastatic patients with an agreement of 88% of participants (37) (Figure 1B).…”
Section: Distant Metastatic Stagingmentioning
confidence: 99%
“…Therefore, more accurate, faster, and non-invasive staging techniques are needed to improve the outcomes from BCa. Given its superior contrast resolution and the addition of functional sequences, MRI has proved to be the best imaging modality for local staging [9]. Several studies have tested its ability to differentiate NMIBC from MIBC and two recent meta-analysis have shown a pooled sensitivity of 87% and 92% and a specificity of 79% and 87%, respectively [10,11].…”
Section: Introductionmentioning
confidence: 99%